Utilization of Social Media to Promote Trademark and Services and Their Legal Protection - A Aflah (Jurnal Jurisprudence, 2018)
Technological advancements continue to evolve all the time, it cannot be hindered and repressed. Thus, such advances must be directed for the good and welfare of human life, including the development of social media-which are currently offered in various forms. Many benefits can be obtained from social media, among others, as a means to promote trademarks and services from producers to consumers. Promotion of trademarks and services through social media provides convenience and benefits for producers, since it can save cost and time. However, advertisement by using social media also has impact on the trademark law in Indonesia. The widespread use of Internet in the trade sector has brought a lot of consequences on the protection of trademark. Owners of trademarks or services obtain legal protection after they are applied and officially registered. Registered trademark is currently protected by Law No. 20 of 2016 concerning Trademark and Geographical Indications.